1998
DOI: 10.31399/asm.cp.itsc1998p0139
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Clearance Control Wear Mechanisms for Low Temperature Aluminium Silicon Alloys

Abstract: Aluminium silicon alloys have shown favourable properties when used as the matrix for abradable coatings in low pressure compressors of gas turbines [1 and 2]. This paper aims to describe the wear mechanisms found in aluminium silicon based abradables. To this end three thermally sprayed coatings are investigated. Aluminium silicon polyester, aluminium silicon-graphite and the most recently developed, aluminium silicon-hexagonal boron nitride (hBN) examined here are amongst a few of these materials. To be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The blade tip velocity was selected to identify how this influenced the blade tip interaction with the abradablecoating. [5].The coatingcharacteristics of the AlSi-hBN are shown in Table 2. Flat Ti-6Al-4V blades were manufactured with a nominalbladelengthof 10mm and thicknessof 0.7mm.…”
Section: Test Parametersmentioning
confidence: 99%
“…The blade tip velocity was selected to identify how this influenced the blade tip interaction with the abradablecoating. [5].The coatingcharacteristics of the AlSi-hBN are shown in Table 2. Flat Ti-6Al-4V blades were manufactured with a nominalbladelengthof 10mm and thicknessof 0.7mm.…”
Section: Test Parametersmentioning
confidence: 99%
“…Ghasripoor et al [8] studied the damage mechanisms of three aluminium-based sealing coatings. They found that, in most cases, blade damage was reduced or replaced by coating adhesion.…”
Section: Introductionmentioning
confidence: 99%